Stakeholder Collaboration Assistance Model in Village Planning and Budgeting - Jopang, Jopang; Tuwu, Darmin; Unga, Wa Ode Harliyanti; Darwin, La Ode Ahmad; Rosika, Rosika (Jurnal Manajemen Pelayanan Publik, 2025)
Village planning and budgeting in Indonesia is now reaping many problems, including human resources and the planning and budgeting model applied to several village heads in the country. One of the areas studied in Indonesia is Southeast Sulawesi Province with research locations in Muna Regency, namely 7 seaside villages and 8 non-seaside villages. This research aims to develop a collaborative mentoring model to improve the effectiveness of village planning and budgeting. This study uses a qualitative approach with a case study method in Muna Regency, Southeast Sulawesi, involving 15 villages with document analysis and in-depth interviews. Based on research that has been carried out, the village documents in Muna Regency already have village medium-term development plan documents, but most villages have expired village medium-term development plan documents. In addition, village assistance in budgeting has also not been maximized, such as the number of budgets in the field of community empowerment that are not planned in the deliberations of the village community development plan but then appear when the village revenue and expenditure budget changes and most of the activities are repeated for less than 4 (four) years. For an effective mentoring model in village planning and budgeting is the Stakeholders Collaborative Model in Village Planning and Budgeting in Muna Regency involving Ministries, Provincial Governments, Regency/City Regional Governments, District Governments, Village Community empowerment cadres and/or Third Parties.